2021
DOI: 10.1039/d0ra09326b
|View full text |Cite
|
Sign up to set email alerts
|

A computational perspective on the dynamic behaviour of recurrent drug resistance mutations in the pncA gene from Mycobacterium tuberculosis

Abstract: Tuberculosis is still one of the top 10 causes of death worldwide, particularly with the emergence of multidrug-resistant tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, these studies are computationally intensive and are difficult to scale for studying hundreds of mutations. A recent MD study on a subset of mutations found within our dataset analysed seven pncA nsSNPs (F94L, F94S, K96N, K96R, G97C, G97D, and G97S) showed that these destabilising mutations altered the binding pocket, allowing increased PZA flexibility ( Khan et al, 2021 ). All seven mutations were associated with PZA resistance and also showed destabilising effects in our study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, these studies are computationally intensive and are difficult to scale for studying hundreds of mutations. A recent MD study on a subset of mutations found within our dataset analysed seven pncA nsSNPs (F94L, F94S, K96N, K96R, G97C, G97D, and G97S) showed that these destabilising mutations altered the binding pocket, allowing increased PZA flexibility ( Khan et al, 2021 ). All seven mutations were associated with PZA resistance and also showed destabilising effects in our study.…”
Section: Discussionmentioning
confidence: 93%
“…The motivation for investigating the missense mutations within the protein coding region only of the pncA gene was to enable understanding of the phenotypic mutational effects in relation to PZA resistance development. While the exact molecular mechanisms of PZA resistance are yet to be fully elucidated, the binding pocket of PZA and its key interactions are well known and characterised ( Petrella et al, 2011 ; Ali et al, 2020 ; Sheik Amamuddy et al, 2020 ; Khan et al, 2021 ). This knowledge was used to guide the molecular docking of PZA to generate the pncA-PZA complex in the absence of an experimentally solved structure of the bound complex in Mtb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the middle of the last century, drug-resistant forms of TB were identified. A rapid spread of antibiotic-resistant strains of Mtb was observed, on which standard chemotherapy has practically no effect [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In the future, worsening of the situation should be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Computational methods are of great interest in exploring biological mechanisms and designing therapeutics against the emerging pathogens (21,22). This also involves the application of computational vaccinology approaches to design vaccine therapeutics.…”
Section: Introductionmentioning
confidence: 99%